2000
DOI: 10.1152/jappl.2000.88.3.1103
|View full text |Cite
|
Sign up to set email alerts
|

Iron supplementation improves endurance after training in iron-depleted, nonanemic women

Abstract: Our objective was to investigate the effects of iron depletion on adaptation to aerobic exercise, assessed by time to complete a 15-km cycle ergometer test. Forty-two iron-depleted (serum ferritin <16 microg/l), nonanemic (Hb >12 g/dl) women (18-33 yr old) received 100 mg of ferrous sulfate (S) or placebo (P) per day for 6 wk in a randomized, double-blind trial. Subjects trained for 30 min/day, 5 days/wk at 75-85% of maximum heart rate for the final 4 wk of the study. There were no group differences in baselin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
163
6
7

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(186 citation statements)
references
References 29 publications
10
163
6
7
Order By: Relevance
“…4,[18][19][20][21] In the present study, increased Hb or higher maximal V : O 2 did not explain the improved exercise endurance. Although Hb levels were slightly higher after iron therapy (nonsignificant), there was no significant correlation with exercise endurance time (data not shown), which corresponds with previous findings in iPAH patients where the absence or presence of anemia did not influence 6MWD.…”
Section: Iron and Exercise Capacitycontrasting
confidence: 67%
“…4,[18][19][20][21] In the present study, increased Hb or higher maximal V : O 2 did not explain the improved exercise endurance. Although Hb levels were slightly higher after iron therapy (nonsignificant), there was no significant correlation with exercise endurance time (data not shown), which corresponds with previous findings in iPAH patients where the absence or presence of anemia did not influence 6MWD.…”
Section: Iron and Exercise Capacitycontrasting
confidence: 67%
“…17 However, the effect size for quality of life appears to be smaller than for fatigue alone; thus, our study was underpowered to reveal a significant effect. Positive effects on physical and psychological performances can be explained by the known effects of iron, which include improving aerobic adaptation, endurance capacity, 15,18,19 muscle fatigability, 20,21 restless leg syndrome, 22 memory, verbal learning and cognitive function. [23][24][25] The effects of iron deficiency on fatigue can be explained by decreased activity of irondependent enzymes; for example, those affecting the metabolism of neurotransmitters that enhance neurophysiologic changes.…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported that, onfortified spreads peanut can be used as supplementary foods instead; these are energy-dense, lipid-based pastes with added powdered micronutrients [5].…”
Section: Issn: 2320-5407mentioning
confidence: 99%